Respuesta :
minus 2πr² both sides
S-2πr²=2πrh
divide both sides by 2πr
[tex] \frac{S-2\pi r^2}{2 \pi r} =h[/tex]
S-2πr²=2πrh
divide both sides by 2πr
[tex] \frac{S-2\pi r^2}{2 \pi r} =h[/tex]
The rearrangement of the formula S = 2πrh + 2πr2 for h is [tex]h = \frac{S - 2 \pi r^2}{2 \pi r}[/tex].
Given that,
- [tex]S = 2 \pi rh + 2 \pi r^2[/tex]
- We have to arrange the above formula for h.
Based on the above information, the calculation is as follows:
[tex]S = 2 \pi rh + 2 \pi r^2[/tex]
Here we have to deduct [tex]2 \pi r^2[/tex] from both the sides.
Now
[tex]S - 2 \pi r^2 = 2 \pi rh[/tex]
Now divide [tex]2 \pi r[/tex] from both sides
So,
[tex]h = \frac{S - 2 \pi r^2}{2 \pi r}[/tex]
Therefore we can conclude that the rearrangement of the formula S = 2πrh + 2πr2 for h is [tex]h = \frac{S - 2 \pi r^2}{2 \pi r}[/tex].
Learn more: brainly.com/question/10726356